Does Transformational Leadership and Organizational Culture Affect Organizational Commitment to Improving the Performance of Employees? - Achmad, Ruth Natalia; Djamil Mz, Masydzulhak (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This research aims to find out the influence of transformational leadership and organisational culture on organisational commitment, which then influences the performance of the Maluku Provincial Forestry Service employees. Methodology/approach – The research method is causal quantitative through collecting employee response data with questionnaires and processing with the SEM-PLS technique using SmartPLS3.2.9. The study population consisted of 135 employees of the Maluku District Forestry Service. The sampling technique used was a saturated sample where the entire population was sampled because the population size was relatively small. Findings – It found a positive and significant direct relationship between transformational leadership and organisational commitment, organisational culture, organisational commitment, organisational commitment to employee performance and organisational culture to organisational performance. This study also found that the relationship of transformational leadership had no positive and insignificant effect on organisational performance. Regarding indirect ties, both the relationship between transformational leadership on employee performance and the relationship between organisational culture on employee performance which is mediated by organisational commitment, show a positive and significant relationship.